The DisVis and PowerFit Web Servers: Explorative and Integrative Modeling of Biomolecular Complexes. Issue 3 (3rd February 2017) - van Zundert, G.C.P.; Trellet, M.; Schaarschmidt, J.; Kurkcuoglu, Z.; David, M.; Verlato, M.; Rosato, A.; Bonvin, A.M.J.J.
Abstract: Structure determination of complex molecular machines requires a combination of an increasing number of experimental methods with highly specialized software geared toward each data source to properly handle the gathered data. Recently, we introduced the two software packages PowerFit and DisVis. These combine high-resolution structures of atomic subunits with density maps from cryo-electron microscopy or distance restraints, typically acquired by chemical cross-linking coupled with mass spectrometry, respectively. Here, we report on recent advances in both GPGPU-accelerated software packages: PowerFit is a tool for rigid body fitting of atomic structures in cryo-electron density maps and has been updated to also output reliability indicators for the success of fitting, through the use of the Fisher z -transformation and associated confidence intervals; DisVis aims at quantifying the information content of distance restraints and identifying false-positive restraints. We extended its analysis capabilities to include an analysis of putative interface residues and to output an average shape representing the putative location of the ligand. To facilitate their use by a broad community, they have been implemented as web portals harvesting both local CPU resources and GPGPU-accelerated EGI grid resources. They offer user-friendly interfaces, while minimizing computational requirements, and provide a first interactive view of the results. The portals can be accessed freely after registration viahttp://milou.science.uu.nl/services/DISVIS andhttp://milou.science.uu.nl/services/POWERFIT . Graphical Abstract: Highlights: Core-weighted local cross-correlation and edge-enhancing Laplace filter in PowerFit New occupancy analysis and statistics for interacting residues in DisVis Grid-based, GPGPU-enabled modular web portals Web portals with advanced post-processing for online visualization of the results